A Case of Angiomyolipoma Rarely Located in the Larynx - Hulya Eyigor; Dinc Suren; Ustun Osma; Cem Sezer; Mustafa Deniz Yilmaz (Case Reports in Otolaryngology)
Angiomyolipoma is a rare benign mesenchymal tumor, which is mostly renal in origin. A sixty-year-old male patient with the diagnosis of angiomyolipoma located in the larynx has been presented here, and the literature is reviewed.